2017
DOI: 10.1159/000468984
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate-Induced Nephrotoxicity in Rats: Protective Effect of Mistletoe (<b><i>Viscum album</i></b> L.) Extract

Abstract: Background: The protective effect of mistletoe extract (Helixor®, HLX) against methotrexate (MTX)-induced acute oxidative stress and nephrotoxicity in rats was evaluated by histological and biochemical methods as well as the comet assay. Material and Methods: 32 female Wistar albino rats were divided into 4 groups: control group, HLX group (5 mg/kg body weight (bw), days 1-10, intraperitoneally (i.p.)), MTX group (10 mg/kg bw, days 7, 8, and 9, i.p.), and MTX + HLX group (10 mg/kg bw, days 7, 8, and 9, i.p. + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
(69 reference statements)
0
4
0
1
Order By: Relevance
“…Therefore plasma MTX concentration monitoring, adequate hydration, urine alkalization and using glucarpidase are recommended during treatment to facilitate renal elimination. 8 Mechanistically, the link between OS and other signaling pathways is well understood. It has been reported that OS can play a role in the development of a variety of diseases by activating the inflammatory response, inducing apoptosis and cell death; furthermore, OS decreases the expression of NRF-2, with the consequent down-regulation of antioxidant genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore plasma MTX concentration monitoring, adequate hydration, urine alkalization and using glucarpidase are recommended during treatment to facilitate renal elimination. 8 Mechanistically, the link between OS and other signaling pathways is well understood. It has been reported that OS can play a role in the development of a variety of diseases by activating the inflammatory response, inducing apoptosis and cell death; furthermore, OS decreases the expression of NRF-2, with the consequent down-regulation of antioxidant genes.…”
Section: Discussionmentioning
confidence: 99%
“…most notably renal and liver toxicity as well as duodenal damage, 7 and bone marrow toxicity. 8 Methotrexate-induced renal toxicity has been related to several different damage pathways, comprising oxidative stress and inflammatory reactions, mitochondrial dysfunction, and lastly, apoptosis. 9 Vitamin B6, a member of the water-soluble vitamin family, is made up of three related compounds: pyridoxine, pyridoxal, and pyridoxamine; 10 as shown in Figure 2 (structure 1).…”
Section: Research Articlementioning
confidence: 99%
“…Helixor M, extract from Viscum album L. growing on apple tree, showed activity against methotrexate (MTX)-induced acute oxidative stress and nephrotoxicity in rats. The mechanism included antioxidant and anti-inflammatory properties, as evident from significant increase in the activities of the antioxidative enzymes, superoxide dismutase (SOD) and glutathione peroxidise (GSH-Px) (Sakalli Çetin et al 2017). Oleanolic acid isolated from Viscum articulatum Burm.…”
Section: Nephroprotective and Antidiuretic Activitymentioning
confidence: 99%
“…Aber warum ist das so? Die dritte Publikation in dieser Ausgabe der CMR zum Einsatz der Mistel beim Tier ist -anhand eines Laborversuchs mit Ratten -ein Beitrag zur Aufklärung der Wirkmechanismen der Nebenwirkungsreduktion einer durch den chemotherapeutischen Wirkstoff Methotrexat induzierten Nierenschädigung [14].…”
Section: Labortiereunclassified